ICT IMPLEMENTATION IN THE SYSTEM OF TEACHER EDUCATION: NORDIC DIMENSION - Angelina O. Roliak (Information technologies and learning tools, 2019)
The main subject of the research is implementation of information and communication technologies in teacher education system of Nordic countries. The article offers a comparative analysis of the main stages in the ICT development in the professional teacher training systems of four developed countries in the Scandinavian region: Denmark, Norway, Sweden and Finland, which are world leaders in the impact of ICT on education and society and have gained a positive experience in creating their own strategies for reforming of all the important teacher education components based on the widespread use of modern information and communication technologies. The author considers that one of the key factors explaining Nordic innovation and digital literacy strength lies in the fact that the progress of using ICT in the system of professional teacher training has taken place in parallel with the processes of informatization, computerization, technological changes and prioritization of the 21-st century skills development in all countries of the Nordic region. Three essential stages of ICT implementation in Nordic educational environment were substantiated. The first is induction (or introductory) stage, connected with the gradual implementation of computer technologies into the educational process. The second is infusion (or partial use) stage, distinguished by joining all the educational institutions to the worldwide information systems. The third is incorporation (or systematic integration) stage, identified by the conceptualization of ICT-related teacher education. These three stages are characterized by the main similar and different principles of the information technologies use in the Nordic pedagogic dimension. The research findings may help to efficiently implement the information and communication technologies into the system of Ukrainian teacher education.